Abdominal Obesity - Erica Bub; Karla Shelnutt; Gail Kauwell (EDIS)
Santa Claus, Winnie the Pooh®, and Shrek® … what do these three characters have in common? You probably know them for being jolly and for having extra fat around their waists, also known as “abdominal obesity.” Although this may be cute in fairy tales or movies, abdominal obesity can be a serious health risk in the real world. Abdominal obesity, also known as central adiposity, is a buildup of fat tissue around the waist or midsection. It is a risk factor for certain health conditions. Read this 4-page fact sheet to find out more about the health risks of abdominal obesity and ways to prevent or treat it. Written by Erica Bub, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, February 2013.